La disciplina y su incidencia en la enseñanza aprendizaje en la escuela “José Isaac Montes” - Cedeño Mendoza, Teresa Mariana (2021)
The research carried out assumes as a problem: How to improve student discipline in the “José Isaac Montes” School of Basic Education? In order to solve the problem, the general objective was formulated: To develop strategies to improve discipline in the teaching-learning process of the students of the “José Isaac Montes” school. To achieve this, the researcher relied on the mixed research approach and applied research, and from this point of reference, the dialectical method, empirical survey and observation methods, the PNI technique (Positive, Negative and Interesting), specialist criteria and a workshop were used. socialization with users and the descriptive statistical method; which allowed to carry out the research and reach the following conclusions: The strategies applied to improve discipline in the teaching-learning process served as an instrument to achieve the objectives proposed in the students, since it was applied in an optimal and constant way to improve the discipline in students. The realization of trainings and workshops, as well as meetings were of great importance since the way of acting of the students from home was known, the influence that parents have on their children, how the teacher handles a situation before an act of bad discipline, in addition to how issues influence student performance, essential values were developed for students and issues were dictated that make students change their way of acting in the classroom, at home and in any social context.